Bone marrow cell homing to sites of acute tibial fracture: (89)Zr-oxine cell labeling with positron emission tomographic imaging in a mouse model - Asiedu, Kingsley O. (EJNMMI Res, 2018)
BACKGROUND: Bone fracture healing is dependent upon the rapid migration and engraftment of bone marrow (BM) progenitor and stem cells to the site of injury. Stromal cell-derived factor-1 plays a crucial role in recruiting BM cells expressing its receptor CXCR4. Recently, a CXCR4 antagonist, plerixafor, has been used to mobilize BM cells into the blood in efforts to enhance cell migration to sites of injury presumably improving healing. In this study, we employed zirconium-89 ((89)Zr)-oxine-labeled BM cells imaged with positron emission tomography (PET)/computed tomography (CT) to visualize and quantitate BM cell trafficking following acute bone injury and to investigate the effect of plerixafor on BM cell homing. Unilateral 1-mm incisions were created in the distal tibia of mice either on the same day (d0) or 24 h (d1) after (89)Zr-oxine-labeled BM cell transfer (n = 4–6, 2–2.3 × 10(7) cells at 9.65–15.7 kBq/10(6) cells). Serial microPET/CT imaging was performed and migration of (89)Zr-labeled cells to the bone injury was quantified. The effects of three daily doses of plerixafor on cell trafficking were evaluated beginning on the day of fracture generation (n = 4–6). The labeled cells localizing to the fracture were analyzed by flow cytometry and immunohistochemistry. RESULTS: In d0- and d1-fracture groups, 0.7% and 1.7% of administered BM cells accumulated within the fracture, respectively. Plerixafor treatment reduced BM cell migration to the fracture by approximately one-third (p < 0.05 for both fracture groups). Flow cytometry analysis of donor cells collected from the injured site revealed a predominance of CD45(+) stem/progenitor cell populations and subsequent histological analysis demonstrated the presence of donor cells engrafted within sites of fracture repair. CONCLUSION: (89)Zr-oxine labeling enabled visualization and quantitation of BM cell recruitment to acute fractures and further demonstrated that plerixafor plays an inhibitory role in this recruitment. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13550-018-0463-8) contains supplementary material, which is available to authorized users.